Contacts and Contrasts in Cultures and Languages - Lewandowska-Tomaszczyk, Barbara (Issues in Literature and Culture, 2019)
This volume provides descriptions and interpretations of social and cognitive phenomena as well as processes that emerge at the interface of languages and cultures in the context of contrastive and contact linguistics and media discourse. Different contexts are explored with rich empirical findings and authentic exemplifying materials. The book includes fifteen papers, divided into three parts. Part 1 addresses conceptual reflection on languages and cultures in contact and contrast, while Part 2 focuses on contact linguistics and borrowing. Part 3 discusses cultural and linguistic aspects of media discourses.